Canadian and Nepali Counsellors: In Collaboration for Social Justice in Nepal - Keats, Patrice A.; Sharma, Ashwin (Canadian Journal of Counselling and Psychotherapy, 2014)
From social justice roots, Canadian counsellors are starting to collaborate with counsellors and communities in international developing countries. In this article, we outline the work of a group of Canadian counsellors who volunteer to collaborate with, educate, and consult with local lay counsellors in our centre in Pokhara, Nepal, called Nepal House Kaski. Using an emancipatory communitarian approach to social justice practices, we explore our approach to working with Western counselling processes in the Nepali culture and how these new interventions for Nepali practitioners bring some challenges to the work of assisting and supporting traumatized Nepali children. Possible research questions and methods are suggested as a collaborative means of assessing our influence and progress toward better mental health for Nepali children.